Benefits of Work-Integrated Learning: Perceptions Held by Chinese International Students Enrolled in an Australian University and Managers in the Chinese Hotel Industry. Issue 3 (3rd July 2019) - Sonnenschein, Katrine; Barker, Michelle; Hibbins, Ray
ABSTRACT: This article explores the perceptions held by 2 stakeholder groups regarding the usefulness of work-integrated learning (WIL) in the hotel industry as part of tourism and hospitality students' overseas studies. The 2 stakeholder groups are Chinese international students enrolled in tourism and hospitality degrees at a particular Australian university and managers working in the Chinese hotel industry. The findings from 31 interviews suggest that both groups have clear perceptions of the outcomes of the WIL component, including the ability of such experiences to bridge theory and practice and to develop the graduate attributes needed for employability in China. The study also explores themes regarding the particular university's role in investigating and securing work placements within the Australian and Chinese contexts. The article recommends that internship programs be embedded in the tourism and hospitality degrees at the particular university and that engagement with the Chinese hotel industry be enhanced.